2013
DOI: 10.1371/journal.pone.0063585
|View full text |Cite
|
Sign up to set email alerts
|

Hnf-1β Transcription Factor Is an Early Hif-1α-Independent Marker of Epithelial Hypoxia and Controls Renal Repair

Abstract: Epithelial repair following acute kidney injury (AKI) requires epithelial-mesenchyme-epithelial cycling associated with transient re-expression of genes normally expressed during kidney development as well as activation of growth factors and cytokine-induced signaling. In normal kidney, the Hnf-1β transcription factor drives nephrogenesis, tubulogenesis and epithelial homeostasis through the regulation of epithelial planar cell polarity and expression of developmental or tubular segment-specific genes. In a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Mutation or defects in HNF-1␤ lead to various renal diseases including cystic kidneys (41). HNF-1␤ has also been reported to associate with renal epithelial cell survival that may drive recovery and repair of kidney from ischemic injury (42). Our current study has demonstrated the first evidence for a protective role of HNF-1␤ in cisplatin nephrotoxicity.…”
Section: Discussionmentioning
confidence: 52%
“…Mutation or defects in HNF-1␤ lead to various renal diseases including cystic kidneys (41). HNF-1␤ has also been reported to associate with renal epithelial cell survival that may drive recovery and repair of kidney from ischemic injury (42). Our current study has demonstrated the first evidence for a protective role of HNF-1␤ in cisplatin nephrotoxicity.…”
Section: Discussionmentioning
confidence: 52%
“…43 In addition, during AKI, HNF-1b regulated the expression of genes important for homeostasis control, repair, and the state of epithelial cell differentiation. 44 A shortcoming of our study is the fact that we could not obtain detailed data on the probable cause of CKD for all patients (we obtained the probable cause of CKD for 91.4% of the patients) and that we lacked information on comorbidities. Therefore, there may be a potential selection bias or unknown (comorbidity) confounder effect.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 Hnf1b directly regulates the expression of Pkhd1 in tubular epithelial cells that are involved in tubulogenesis in the kidney, 82,83 and Socs3 which is essential for renal repair. 84 Although Hnf1a is expressed in the developing kidney and plays a role in kidney development, it is also a key regulator of numerous essential metabolic processes during adulthood. These include maintaining glucose homeostasis through regulation of the glucose-6-phosphatase system and the glucose transporter, as well as regulating other transporters that impact on the metabolism of amino acids because of impaired renal reabsorption.…”
Section: Key Pointmentioning
confidence: 99%